Semi active seat suspension system using modified intelligent active force control - Rosmazi, Rosli; Zamri, Mohamed; Priyandoko, G. (Universiti Malaysia Pahang, 2021)
This paper presents a modified intelligent active force control (AFC) control strategy in a semi active seat suspension system. The main actuator studied in this research is the Magneto-rheological (MR) damper. Since a semi-active device like MR damper can only dissipate energy so a modified version of AFC controller is needed. The modified AFC controller main function is to determine the appropriate control force. A Heaviside Step Function (HSF) is used to ensure the MR damper produce the desired damping force according to the control force generated by AFC controller. The phenomenological Bouc-Wen is used to study the effectiveness of the new AFC controller taking into account the dynamic response of the damper. Sinusoidal signals simulated as vibration sources are applied to the seat suspension system to investigate the improvement of ride comfort as well as to ascertain the new AFC controller robustness. Comparison of body acceleration signals from the passive suspension with AFC controller semi active seat suspension system shows up to to 45% improvement to the occupant ride comfort under different vibration intensities.